2008
DOI: 10.1152/japplphysiol.01135.2007
|View full text |Cite
|
Sign up to set email alerts
|

Training at high exercise intensity promotes qualitative adaptations of mitochondrial function in human skeletal muscle

Abstract: This study explored mitochondrial capacities to oxidize carbohydrate and fatty acids and functional optimization of mitochondrial respiratory chain complexes in athletes who regularly train at high exercise intensity (ATH, n = 7) compared with sedentary (SED, n = 7). Peak O(2) uptake (Vo(2max)) was measured, and muscle biopsies of vastus lateralis were collected. Maximal O(2) uptake of saponin-skinned myofibers was evaluated with several metabolic substrates [glutamate-malate (V(GM)), pyruvate (V(Pyr)), palmit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
57
1
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 84 publications
(69 citation statements)
references
References 46 publications
9
57
1
2
Order By: Relevance
“…IHE raises the question of the minimum duration of exposure to induce erythropoiesis. It has been suggested that 180 min of IHE daily are necessary to increase endogenous erythropoietin (EPO), but in the vast majority of protocols this appears to be inconsistent [19,40,75,148]. Cerebral oxygenation decreases, whereas muscle oxygenation increases due to a greater ability to extract O 2 in order to 8 counteract reduced O 2 availability, as shown by a decreased deoxyhaemoglobin during heavy exercise [92], 2) Intermittent hypoxic training (IHT) consists of physical activity under hypoxic conditions (for short periods, and remaining at normoxic conditions for the rest of the time.…”
Section: Methods Of Hypoxic Exposure and Of Hypoxic Trainingmentioning
confidence: 99%
“…IHE raises the question of the minimum duration of exposure to induce erythropoiesis. It has been suggested that 180 min of IHE daily are necessary to increase endogenous erythropoietin (EPO), but in the vast majority of protocols this appears to be inconsistent [19,40,75,148]. Cerebral oxygenation decreases, whereas muscle oxygenation increases due to a greater ability to extract O 2 in order to 8 counteract reduced O 2 availability, as shown by a decreased deoxyhaemoglobin during heavy exercise [92], 2) Intermittent hypoxic training (IHT) consists of physical activity under hypoxic conditions (for short periods, and remaining at normoxic conditions for the rest of the time.…”
Section: Methods Of Hypoxic Exposure and Of Hypoxic Trainingmentioning
confidence: 99%
“…In a previous study, we showed that V max was positively correlated to V O 2max when the population ranges from sedentary (V O 2max ϭ 28.5 ml·kg Ϫ1 ·min Ϫ1 ) to moderately trained subjects (V O 2max ϭ 50 ml·kg Ϫ1 ·min Ϫ1 ) (51). However, in subsequent studies, endurance athletes with higher V O 2max (ϳ60 ml·kg Ϫ1 ·min Ϫ1 ) were shown to have similar V max values compared with their moderately trained counterparts (12,34), suggesting that the quantitative aspects of tissue oxidative capacity levels off before the highest levels of endurance training are reached. Moreover, the higher V O 2max demonstrated by endurance-trained athletes was not accompanied by any increase in enzymatic markers of quantitative aspects of mitochondrial function (34).…”
Section: Maintenance Of V O 2max and Maximal A-vo 2 Difference In Hypmentioning
confidence: 96%
“…Physical activity increases skeletal muscle energy demand many fold, and it is not surprising that cross-sectional studies suggest an association between physical activity levels and changes in both mitochondria content [33][34][35][36] and function [33,[37][38][39][40]. Interestingly, analysis of the cross-sectional data published to date indicates that higher physical activity levels are associated with relatively larger values for mitochondrial function (as measured by mitochondrial respiration) than content (as measured by Citrate Synthase activity) (Fig 1).…”
Section: Can We Optimise Exercise Training To Improve Mitochondrial Fmentioning
confidence: 98%